Analisis Kelayakan Finansial dan Sensitivitas Usaha Hidroponik PT. XYZ di Kabupaten Bogor - Veralinta Br Sebayang; Elysabeth July Aini Sinurat; Ajeng Anjani; Aldo Abiyyu Dzaki Hamdan; Miqdad Hafidz Rabbani; Muhamad Rafli (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the financial feasibility and sensitivity of PT. XYZ’s hydroponic business in Bogor Regency against production cost escalations. Primary and secondary data were evaluated using Net Present Value (NPV), Gross Benefit-Cost Ratio, Net Benefit-Cost Ratio, Internal Rate of Return (IRR), and Payback Period. Sensitivity analysis was simulated across 10%, 15%, and 20% cost increase scenarios. Initial results confirm investment feasibility, yielding an NPV of IDR 71,592,208 and an IRR of 10.54%. However, profitability proves highly vulnerable. Under a 20% operational cost increase, the business reaches the feasibility threshold, suffering a 33.81% drop in NPV. While fundamentally viable, maintaining operational stability requires strict management control over the input cost structure.